Managing yourself - Walmsley, Bernice (Instant manager, 2010)
Part of a vital series for today's manager, produced in conjunction with the Chartered Management Institute, 'Instant Manager: Managing Yourself' is for managers who want to take their career all the way. Practical and down to earth, it concludes with a fascinating interview with Andy Green, CEO of Logica